THE USE OF WORDWALL BASED EDUCATIONAL GAMES IN ENHANCING STUDENTS LEARNING ENTHUSIASM - Faizatul Widat; Siti Hadiatus Sakdiyah (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
This study aims to describe the implementation of Wordwall-based educational games in improving students’ learning enthusiasm at MI Zainul Anwar. This research employed a qualitative descriptive approach. The participants consisted of teachers and students who were directly involved in the learning process. Data were collected through observation, interviews, and documentation. The results indicate that the use of Wordwall creates a more interactive, engaging, and student-centered learning environment. Students showed increased attention, participation, and interest during the learning activities. Teachers acted as facilitators by providing guidance and feedback, which supported an effective and enjoyable learning atmosphere. However, the findings of this study cannot be generalized to all educational institutions, as they are influenced by school conditions, student characteristics, teacher readiness, and the availability of supporting facilities. Therefore, the use of Wordwall-based educational games can serve as an alternative learning medium to enhance students’ learning enthusiasm at MI Zainul Anwar, provided that it is adapted to the specific context and needs of the school.